Promoting intergenerationality at casa pousio - is casa pousio financially viable - Simões, Nuno Sérgio Camelo (2024)
AMUT’s mission is to foster the well-being of individuals by enhancing health and overall happiness. In response to the pressing challenges of housing affordability and social isolation in Portugal, Casa Pousio’s project emerged. It goes beyond typical housing, aiming to create a unique community where different generations collaborate, promoting intergenerationality. It seeks to revolutionise living, becoming Portugal’s first Blue Zone – a community where residents enjoy longer, healthier lives. This analysis explores potential activities for Casa Pousio’s communal spaces, encouraging intergenerational interactions and knowledge exchange, and assesses the project’s financial viabilit.